Uncovering the Way of K-Pop as a Cultural Diplomacy Strategy South Korea in Indonesia - Ismail, Achmad (Jurusan Ilmu Hubungan Internasional, 2023)
The popularity of K-Pop in the world, especially in Indonesia, cannot be separated from the efforts of the South Korean government to make K-Pop an instrument of cultural diplomacy. In this way, the popularity of K-Pop contributes to the fulfillment of its national interests. This article aims to analyze the stages of the K-Pop strategy as an instrument of cultural diplomacy by the South Korean government as well as the benefits derived from these efforts. This article uses a descriptive research method with data collection techniques from several books, journals, official documents, and official websites on the internet. This article finds that there are 3 stages of South Korean cultural diplomacy through K-Pop in Indonesia, namely introduction, policy, and cooperation. Through these 3 stages, South Korea gets the benefit, both politically, economically, socially, and culturally as a form of its national interest. This article concludes that South Korean cultural diplomacy through K-Pop with these 3 stages is a certain strategy to popularize K-Pop while at the same time fulfilling its national interests.